Implementasi Manajemen Strategi Pesantren di Era Revolusi Industri 4.0 - Ahmad Hinayatulohi; Iwan Sopwandin; Aep Saepurohman; Asep Abdurahman (Universitas Negeri Malang, 2023)
Abstract: This study aims to describe the implementation of Islamic boarding school strategic management at the IT boarding school in Yogyakarta in the industrial revolution 4.0 era. The method used in this study is a qualitative descriptive analysis approach. The selection of informants in this study used a purposive sampling technique (purposed sample). Data collection techniques were carried out by means of observation, interviews, and documentation studies. Stages of data analysis through data condensation, data presentation and conclusions. The results of this study indicate that Islamic Boarding School Pondok IT Yogyakarta implements strategic management through four stages, namely: First, environmental analysis is carried out in two ways, namely external and internal analysis. External factors, namely the demand for human resources who have the ability in the field of technology is increasing. While the internal factors are a strong leader's commitment; Second, the strategy formulation was made by the Pondok IT Yogyakarta Islamic Boarding School by formulating the vision, mission and objectives as well as curriculum development strategies; Third, strategy implementation is carried out to carry out the plans that have been made in the strategy formulation. At this stage of implementation, there is a religious learning process that is integrated with technology, namely a YouTube based online recitation which is held every morning; and Fourth, the strategic evaluation of the Pondok IT Yogyakarta Islamic boarding school was carried out to determine whether the implementation was in accordance with the planned strategy formulation. Evaluation is carried out in several ways, including unannounced inspections and other evaluations using a group evaluation system. Keywords: Strategic management, Islamic boarding school, industrial revolution 4.0 Abstrak: Penelitian ini bertujuan untuk mendeskripsikan implementasi manajemen strategi pesantren di pondok IT Yogyakarta di era revolusi industry 4.0. Metode yang digunakan dalam penelitian ini adalah kualitatif pendekatan deskriptif analisis. Pemilihan informan dalam penelitian ini menggunakan teknik Purposive sampling (sampel bertujuan). Tehnik pengumpulan data dilakukan dengan cara observasi, wawancara, dan studi dokumentasi. Tahapan analisis data melalui kondensasi data, penyajian data dan kesimpulan. Hasil dalam penelitian ini menunjukan bahwa Pesantren Pondok IT Yogyakarta mengimplementasikan manajemen strategi melalui tahapan empat tahapan yaitu: Pertama, analisis lingkungan dilakukan melalui dua cara yaitu analisis eksternal dan internal. Faktor eksternal yaitu permintaan akan sumber daya manusia yang memiliki kemampuan dibidang teknologi meningkat. Sedangkan faktor internal adalah komitmen pemimpin yang kuat; Kedua, formulasi strategi dibuat oleh pesantren Pondok IT Yogyakarta dengan merumuskan visi, misi dan tujuan serta strategi pengembangan kurikulum; Ketiga, implementasi strategi dilakukan untuk melaksanakan rencana yang sudah dibuat dalam formulasi strategi. Pada tahapan implementasi ini, terdapat proses pembelajaran kegamaan yang terintegrasi dengan teknologi yaitu ngaji online berbasis youtube yang dilaksanakan setiap pagi; dan Keempat, evaluasi strategi pesantren Pondok IT Yogyakarta dilakukan untuk mengetahui pelaksanaan apakah sesuai dengan formulasi strategi yang telah direncanakan. Evaluasi dilakukan melalui beberapa cara, antara lain evaluasi bersifat inspeksi mendadak dan evaluasi lain dengan menggunakan sistem evaluasi kelompok. Kata kunci: Manajemen strategi, pesantren, revolusi industri 4.0